Cholesterol Lowering Activity from Methanol Extract of Bidara Leaves (Ziziphus mauritiana) - Isna Lailatusholihah; Weny JA Musa; Lintang Panji Setyoko; Holisha Widiyanto; Nurhayati Bialangi; Boima Situmeang (Stannum : Jurnal Sains dan Terapan Kimia, 2023)
Research on qualitative test of secondary metabolites compounds and test of lowering cholesterol activity has been done on bidara leaves (ziziphus mauritiana) with methanol extract by maceration methods. The aim of this research was to determine cholesterol-lowering activity of methanol extract on bidara leaves (ziziphus mauritiana). The procedure used was in this study consisted of extraction, phytochemicals screening such as alkaloids, tannins, triterpenoids, flavonoids and saponins, and test of cholesterol lowering activity using UV-Vis spectrophotometry at a wavelength of 423 nm. Based on research results, determine cholesterol lowering activity of methanol extract on bidara leaves (ziziphus mauritiana) has proven to reduce cholesterol levels by 80.4598% because of bidara leaves contains of active secondary metabolites such as triterpenoids, tannins and flavanoids.